Спеціальні принципи діяльності відділів прикордонної служби - Ляшук, Р.; Lyashuk, R. (Східноєвроп. нац. ун-т ім. Лесі Українки, 2013)
У статті розглянуто обсяг та значення спеціальних принципів у діяльності відділів прикордонної служби. Проаналізовано зміст спеціальних принципів, що стосуються правоохоронної діяльності відділів прикордонної служби. Унаслідок дослідження нормативно-правових актів із питань охорони державного кордону автор визначає зміст спеціальних принципів у діяльності відділів прикордонної служби.The article deals with the meaning of special principles of Border Service departments’ activity. Contents of special principles relating to law enforcement activities of Border Service departments are analyzed. The main special principles of the Border Service department activity are: extensive use of open and secret forms and methods of the state border protection; the continuous obtaining the information and its timely realization for the border protection; departments’ constant readiness for action, complex application of different forces and resources; the continuity and flexibility of the border protection; expediency of the border protection and border control organization; maneuverability of forces and assets, activity, secrecy and rapidity of action, selectivity of control actions and risk assessment process, automating and continuity of the department management process. It’s necessary to open the system of special principles more widely in the new edition of the Instruction of the Border Service departments activity, considering their importance.
Special Principles of the Border Service Department.
Keywords: спеціальні принципи; відділи прикордонної служби; охорона державного кордону; specific principles; border service department; border protection.